Increased vascular deposition of oxidized LDL in untreated juvenile dermatomyositis - Jacob C. Spitznagle; Akadia Kacha-Ochana; Joan M. Cook-Mills; Gabrielle A. Morgan; Lauren M. Pachman (BMC, 2024)
Abstract Background Juvenile dermatomyositis (JDM) is a systemic vasculopathy associated with metabolic derangements and possible increased risk for premature atherosclerosis. Oxidation of low-density lipoprotein (LDL) in the endothelium is an early step in atherosclerotic plaque formation. It is not known if oxidized LDL is altered in children with untreated JDM. The deposition of oxidized LDL in the vasculature of muscle biopsies (MBx) from patients with untreated JDM and pediatric controls was assessed. Findings Frozen tissue sections of MRI-directed MBx from 20 female children with untreated JDM and 5 female controls were stained with DAPI and fluorescently labeled antibodies against von Willebrand factor (vWF) and LDL oxidized by copper (oxLDL). Blood vessels were identified by positive vWF staining, and total fluorescence of oxLDL within the vessel walls was measured. Children with untreated JDM had increased deposition of oxLDL in the walls of muscle vasculature compared to healthy children (difference in means ± SEM = 19.86 ± 8.195, p = 0.03). Within the JDM cohort, there was a trend towards increased oxLDL deposition with longer duration of untreated disease (r = 0.43, p = 0.06). There was no significant correlation found between oxLDL deposition and markers of acute JDM disease activity including disease activity scores or muscle enzymes. Conclusions This study found increased deposition of oxLDL within blood vessels of children with untreated JDM supporting the concern that these children are at increased risk for premature atherosclerosis from chronic exposure to vascular oxLDL. This study highlights the importance of early diagnosis and treatment initiation to ameliorate cardiovascular damage.